An evaluation and replication of miRNAs with disease stage and colorectal cancer‐specific mortality - Slattery, Martha L.; Herrick, Jennifer S.; Mullany, Lila E.; Valeri, Nicola; Stevens, John; Caan, Bette J.; Samowitz, Wade; Wolff, Roger K. (International journal of cancer, 2015)
MicroRNAs (miRNAs) have been implicated in colorectal cancer (CRC) development and associated with prognostic indicators such as disease stage and survival. Prognostic associations are often based on few individuals and imprecise. In this study, we utilize population‐based data from 1,141 CRC cases to replicate previously reported associations between 121 miRNAs and disease stage and survival. The Agilent Human miRNA Microarray V19.0 was used to generate miRNA data following a stringent quality control protocol. Assessment of survival was done using Cox Proportional Hazard models adjusting for age, disease stage and tumor molecular phenotype. Five miRNAs were associated with more advanced disease stage; hsa‐miR‐145‐5p and hsa‐miR‐31‐5p showed increased expression with more advanced tumor stage, while hsa‐miR‐200b‐3p, hsa‐miR‐215 and hsa‐miR‐451a had decreased expression with more advanced tumors. Thirteen miRNAs were associated with CRC mortality among individuals diagnosed with colon cancer while 14 were associated with CRC mortality after a diagnosis with rectal cancer. Strongest associations were observed for those miRNAs that were expressed in a small subset of tumors. Most notable associations were for hsa‐miR‐145‐3p [hazard ratio (HR) 2.94, 95% confidence interval (CI) 1.54, 5.61], and hsa‐miR‐9‐3p (HR 10.28, 95% CI 1.31, 80.84) with colon cancer and hsa‐miR‐335‐5p (HR 0.17, 95% CI 0.05, 0.54) for rectal cancer. hsa‐miR‐374a‐5p, hsa‐miR‐570‐3p and hsa‐miR‐18a‐5p significantly reduced the hazard of dying for all cases, regardless of tumor site. Our findings illustrate the need for a large sample to evaluate the association of miRNAs with survival and disease stage in order to determine associations by tumor site. What's new? MicroRNAs (miRNAs) are promising prognostic biomarkers in colorectal cancer, but more work is needed to identify clinically meaningful stage‐ and survival‐specific associations. The present study attempted to identify those associations for 121 miRNAs using population‐based data for more than 1,140 colorectal cancer patients. Microarray and statistical analyses uncovered five miRNAs associated specifically with more advanced colorectal cancer. Another 25 miRNAs were linked to mortality for either colon cancer or rectal cancer. The large number of patients and the incorporation of data on tumor molecular phenotype facilitated the detection of associations for miRNAs infrequently expressed in the study population.